Reflexões sobre objetos, esculturas e instalações: ensaio sobre quatro obras - Barion, Andre Catunda Serra [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
In this dissertation I propose a discussion of four works I made between 2017 and 2022, bringing reflections about objects, sculptures and installations, and the role of the spectator in the symbolic and material valuation of an artistic object. I present approximations between fetishism, desire, seduction with the materiality and significance of these works in a context of contemporary art analysis.

Nesta dissertação me propus discorrer sobre quatro trabalhos que realizei entre 2017 e 2022, trazendo reflexões acerca de objetos, esculturas, instalações e o papel do espectador na valoração simbólica e material de um objeto artístico. Apresento aproximações entre o fetichismo, o desejo, a sedução com a materialidade e a significação destes trabalhos em um contexto de análise de arte contemporânea.
Reflections on objects, sculptures and installations: essay on four works
Keywords: Arte; Narrativas pessoais; Arte moderna; Instalações (Arte); Escultura